The expanding cultural space: a case study of the Kalmyk diaspora (Buddhism and identity, migrations and modern technologies) - Elza P. Bakaeva (Novye issledovaniâ Tuvy, 2019)
The article analyzes the cultural space defined by different Kalmyk-inhabited territories with a special insight into the life of the U.S. Kalmyk community. It outlines the multi-level ties between Kalmyk-inhabited territories within their common cultural space determined by specific historical destinies of the ethnicity. In the “Iron Curtain” period, any such ties were dramatically dependent upon the misfortunes of history. The illegal act of forced deportation of the Kalmyk population to the Eastern regions of the USSR ‘tore apart’ this cultural space as it scattered the ethnicity itself. Ties with the cultural space manifested themselves only in somewhat persistent historical memory about the ‘mother ethnicity’ cultivated by American Kalmyks, and in their attempts to facilitate the restoration of Kalmykia’s autonomy that would once again reinforce these mutual ties. When the autonomy was reestablished, some cultural contacts were reinstalled, even though the cultural space remained closed off. The contemporary period (from the 1900s onwards) is a time when the cultural space expanded, enriched through the use of Internet technologies. The article also examines the cultural space of the Kalmyk diaspora in terms of certain unifying and distinguishing factors which set up a link between confessional and ethnic identities. The author also sheds light on current processes facilitating the development of an integrated cultural and confessional space, and factors contributing to these developments. Interpreting the newly emerged social conditions and information technologies, the article also analyzes some of the symbols accepted by the U.S. Kalmyk diaspora. Sources for the study include scholarly publications, Internet resources, media articles, as well as the author's field observations during her 2012 stay with the U.S. Kalmyk diaspora and the active epistolary exchange since then.